OPTIMIZATION OF WATERJET THRUST FOR FISHING BOAT USING THE TAGUCHI METHOD - Wahid, Mohammad Abdul; Muzaka, Khairul; Umar, Mega Lazuardi (Aurelia Journal, 2025)
Indonesia is an archipelagic country with vast waters. Therefore, it is necessary to develop water transportation tools that support the exploitation of marine resources. Therefore, this study optimizes the waterjet thrust on fishing boat to determine the impact on fishermen's profits. Simulation to obtain the velocity at the nozzle outlet is carried out using CFD software.The purpose of this study is to obtain Waterjet Design Variation Variables that produce optimum Thrust Force. The design variables varied are the nozzle outlet diameter, the number of stator blades, and the number of rotor blades. Where each design variable has 3 levels and its degrees of freedom are 6. Thus, the Experimental Design uses the L9 orthogonal array matrix. The L9 orthogonal array matrix has 3 columns and 9 rows that can be used for 3 independent variables, each of which has 3 levels. From the test results, the smallest thrust force is 24.46 N in the 3rd Variation. Meanwhile, the highest thrust force is found in Variation 5, with design variables of nozzle outlet diameter of 80 mm, number of rotor blades of 4, and number of stator blades of 6. The highest thrust force is 38.58 N. The design variations that affect the thrust force are nozzle outlet diameter, number of stator blades and number of rotor blades. The results of the research have an impact on making it easier for fishermen to choose the specifications of the waterjet they will use.